PEMBELAJARAN BAHASA ARAB MELALUI METODE UNGZUR WAQUL PADA REMAJA DESA JATIMULYA - Achmad Farhan; Acep Mulyadi; Akmal Rizki Gunawan Hasibuan (Universitas Islam 45 Bekasi, 2022)
Arabic is the second language spoken in Indonesia. Therefore, good and proper methods, systems and principles of learning may contribute to achieving the purpose of Arabic teaching and learning activities. When a teacher does not properly apply methods, systems, and principles, teaching will not be effectively directed. Today, there are many interactive and innovative Arab learning techniques that teachers can apply. Application of methods, systems and principles will surely enhance the students' passion in learning Arabic simultaneously and continuously. The author has done a study of the existence of what is considered most effective. By using the method of look and say. And in running this program the authors involve some of the jatimulya youth that are the object of this learning. Using the enforcement method that is public education. It runs from February 12 to March 14. The program aims to enhance the jatimulya teen's awareness of the importance of Arabic. And from the results of the implementation of the learning program through look and say method, the jatimulya youth are attracted and they are quick to understand the learning that has been taught, and they are happy and active in learning it. With the end result they can speak Arabic